Inside BAR (The Biblical archaeology review, 1984)
In the early centuries of the Common Era, scores of elegant bath complexes were constructed at natural mineral springs throughout the Roman empire. And of all these baths, from Britain to Judea, one of the most magnificent was the seven-pool complex at Hammat Gader in the verdant valley of the Yarmuk River. In "Sumptuous […]